A STRATEGIC PLANNING MODEL FOR THE DEVELOPMENT OF THE E-GOVERNMENT SYSTEM IN THE CONTEXT OF ENSURING INFORMATION SECURITY - KUTOVA, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article proposes a strategic planning model for the development of e-government in Ukraine, with a central focus on ensuring information security. The research is motivated by the intensifying cyber threats accompanying digital transformation and the need for a coherent, staged approach to mitigating security risks in public administration. The author justifies the use of short-term, medium-term, and long-term planning horizons to structure the strategic response to current and anticipated digital vulnerabilities. In the short term, the focus lies on regulatory modernization, particularly aligning national data protection legislation with the EU’s General Data Protection Regulation (GDPR), implementing the Cloud Services Act, and reinforcing human capacity through cybersecurity training for public servants. Institutional coordination is also emphasized, recommending the establishment of a permanent interagency cybersecurity body. The medium-term perspective targets the development of a secure and interoperable national digital infrastructure. This includes deploying certified national cloud systems, achieving full interoperability of government registries, enhancing digital identity platforms such as Diia, and finalizing the adoption and implementation of national AI and data protection strategies. A special emphasis is placed on building the operational capacity of cybersecurity institutions and fostering public-private-academic partnerships similar to those in Estonia and Israel. Long-term priorities involve embedding information security as a default feature of all e-government processes and transitioning to adaptive, AI-enhanced threat detection systems. The author calls for a dynamic legislative framework that can respond flexibly to technological evolution, participation in EU-level rulemaking bodies, and harmonization with European standards such as the EU Cybersecurity Certification Framework and eIDAS regulation. The vision culminates in Ukraine's full integration into the European Digital Single Market and the promotion of «digital democracy», wherein citizens are actively engaged in decision-making processes through open data and participatory digital platforms.
Keywords: e-government; information security; cybersecurity; strategic planning; digital transformation; regulation; digital identity; EU integration